2020
DOI: 10.2217/fon-2020-0823
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Cemiplimab Versus Other Systemic Treatments for Advanced Cutaneous Squamous Cell Carcinoma

Abstract: Aim: To estimate the comparative efficacy of cemiplimab, a programmed cell death protein 1 inhibitor, versus EGFR inhibitors, pembrolizumab and platinum-based chemotherapy in terms of overall survival (OS) and progression-free survival. Patients & methods: We performed an indirect treatment comparison of cemiplimab and other available systemic therapies for patients with advanced cutaneous squamous cell carcinoma. Results: Cemiplimab was associated with benefits in OS (hazard ratios range: 0.07–0.52) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 90 publications
0
27
0
1
Order By: Relevance
“…When we adjusted for between-study differences in patient characteristics using a population-adjusted indirect comparison, 67 the predicted survival estimates for cemiplimab were consistently more favorable than those used in our current analysis. 48,68 This was driven primarily by a higher proportion of patients with metastatic CSCC in the historical SOC studies compared to the cemiplimab trials. Consequently, we expect that our current analysis was conservative in predicted OS.…”
Section: Discussionmentioning
confidence: 99%
“…When we adjusted for between-study differences in patient characteristics using a population-adjusted indirect comparison, 67 the predicted survival estimates for cemiplimab were consistently more favorable than those used in our current analysis. 48,68 This was driven primarily by a higher proportion of patients with metastatic CSCC in the historical SOC studies compared to the cemiplimab trials. Consequently, we expect that our current analysis was conservative in predicted OS.…”
Section: Discussionmentioning
confidence: 99%
“…The expected publication of results of several clinical trials in the next few years should reveal the prospects of using VSV not only in monotherapy, but also in combination with chemotherapeutic agents and checkpoint inhibitors. In particular, the Phase II study (NCT04291105) assesses the safety and efficacy of VSV-IFNB-hNIS in combination with cemiplimab (an anti-PD1 antibody that has been shown to be effective in the treatment of cutaneous squamous cell carcinoma) [ 177 ], with IV vs. IT administration for melanoma treatment, and with IV infusion for hepatocellular carcinoma, non-small cell lung cancer (NSCLC) and endometrial cancer treatment.…”
Section: Oncolytic Viruses In Clinical Trialsmentioning
confidence: 99%
“…The most common adverse events regardless of attribution during or after treatment of CSCC patients with cemiplimab (3 mg/kg) are fatigue (27.0%) and diarrhea (23.5%) [ 99 ]. As well, it was suggested that cemiplimab was correlated with benefits in OS and PFS in CSCC patients versus EGFR inhibitors and pembrolizumab, signifying its great potential in treating CSCC patients [ 100 ]. Cemiplimab monotherapy also could bring about higher OS and PFS than chemotherapy with platinum-based compounds in patients with advanced NSCLC, and so suggesting a potential new therapeutic approach for this patient population [ 101 ].…”
Section: Fda-approved Icismentioning
confidence: 99%